Distribution of VAM Fungi in Nurseries and Plantations of Neem (Azadirachta indica) in Arid Zone of Rajasthan - Mohan, V.; Verma, Neelam; Singh, Y. P. (Indian Forester, 1995)
Occurrence of VAM fungi is ubiquitous and are found in most ecosystems including arid- and semi-arid deserts. A survey for collection of roots and rhizosphere soil samples of neem from various Forest Department nurseries and plantations in arid zone of Rajasthan revealed variation in per cent root infection and number of VAM propagules in the rhizosphere soil samples. It has been observed that mean number of VAM fungal propagules and per cent root infection were greater in plantation samples than in nursery samples. Different VAM fungi have been isolated, of which the genus Glomus is dominant with an exception of Sclerocystis in plantations. Among the Glomus spp., G. fasciculatum is the most predominant one in both nursery and plantation. The significance of these findings is discussed.